KAJIAN SITUASI PELAKSANAAN PREVENTION OF MOTHER-TO CHILD TRANSMISSION (PMTCT) DI RSUD KOTA C JAWA BARAT - Yuanita Ani Susilowati (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
Infection in pregnant women can be caused by several viruses, one of which is Human Immunodeficiency Virus (HIV). Mother-to-child transmission of HIV reaches 2.6% of all cases of HIV-AIDs, and more than 90% of the incidence of HIV in children is transmitted by mothers. The increase in HIV cases in infants occurred in line with the increase in HIV cases in women, namely 20% in 2007, 25% in 2008, and 27% in 2011. Objectives, Programs are developed to reduce the risk of mother-to-child and mother-to-child transmission of HIV. health workers to achieve improvement in maternal health, reduce infant mortality and protect health workers in RSUD city C. Preparation stage, identification of problems in the midwifery unit, shared perceptions of PMTCT. Implementation, seminars on PMTCT, formation of an education team in early screening (early screening) of pregnant women about PMTCT, making standard operating procedures (SOPs) in prenatal HIV screening, SOPs for delivery in HIV positive patients, SOPs in breastfeeding, and techniques breastfeeding for infants with HIV-positive mothers. Finally, evaluating the results of work related to making SOPs and implementing HIV screening for every prenatal patient. In conclusion, the screening format that has been prepared can capture pregnant women who are at high risk of HIV. Suggestion, HIV screening format needs to be integrated with antenatal care form.